Estímulo do processo da maturação dos frutos de tomateiro pela enzima pectinametilesterase - V L Medina , Paulo (Revista Ceres, 2025)
Studies using the application of ripe tomato fruit homogenates and commercial solutions of PME into immature green tomato fruits led to a closer examination of the effect of PME on the ripening behavioral patterns of tomato fruits harvested at 60 per cent of development.